PENGARUH IMPLEMENTASI KEBIJAKAN TAMBAHAN PENGHASILAN TERHADAP MOTIVASI KERJA PEGAWAI DINAS KESEHATAN PROVINSI SULAWESI TENGAH - Nurhidayati, Nurhidayati (Katalogis, 2016)
This study was conducted to determine how much influence the implementation of additional policies on work motivation income civil servants in Central Sulawesi province. This study uses the theory of Van Meter and Van Horn with standard dimensions and policy objectives, resources, communication between the implementing agency, the implementing body characteristics, social, economic and political, disposition / attitude implementers. The method used in the study is survay analytic using cross sectional design of a study to study the dynamics of the correlation between risk factors by means of observation or data collection approach as well. The results showed that the magnitude of the effect of the implementation of additional policies on work motivation of employees earning the provincial health bureau in Central Sulawesi was the degree of correlation moderate to very low-level relations with the interval of the correlation coefficient between 0.172 up to 0.457.